A systematic literature review on affective polarisation, media and digital platforms (2019-2024) - León Ganatios, Luis Eduardo (2025)
The purpose of this article is to present an exploratory study of research trends on the phenomenon of affective polarization, political polarization, media, and digital platforms for a period of 6 years (2019-2024). A review of the literature, including a non-representative sample of 41 academic articles systematically searched on Google Scholar, is conducted to understand current research from the perspective of digital political communication. This review provides an overview of existing cases and future challenges in research on affective polarisation, political polarisation, media, and digital platforms.